Pengaruh Strategi Digital Marketing Terhadap Minat Beli Konsumen Di Era Pandemi Covid-19: Studi Kasus Pada Pengguna Marketplace Shopee Di Provinsi Jawa Barat - Shofwan Azhar Sholihin; Mutiara Annissa Oktapiani (Coopetition : Jurnal Ilmiah Manajemen, 2021)
Shopee is a marketplace from Singapore, and has started to expand the Southeast Asian market since 2015 including Indonesia. Lifestyle changes amid the pandemic have increased the use of digital media to support online shopping activities. The number of E-commerce usage has increased by 38.3% during the Covid-19 pandemic which started from January to July 2020. Shopee, which is under the auspices of the SEA Group company, is able to get the attention of consumers in Indonesia. It is known that in the first quarter of 2020 Shopee received 71.5 million visits and in the second quarter of 2020 there were 93.4 million visits with the number of orders entering the number of 260 million orders or an increase of 130% from the previous. The purpose of this study is to find out what digital marketing strategy is being carried out by Shopee, and how it affects consumer buying interest, especially in West Java Province during the Covid-19 pandemic, as well as what efforts can be made by Shopee to improve digital marketing strategies. they. Based on the results of the research, it is known that there are 3 digital marketing strategies carried out by Shopee, namely marketing techniques that are in accordance with the trend, maximizing digital media as a place of promotion, and implementing the 4C marketing mix which has influenced consumer buying interest by 51.50% and the remaining 48. ,50% is influenced by other factors not examined in this study such as needs, quality products, and so on.